(Review B) "Jain Life Reimagined: An Examination of Jain Practice and Discourse during the Covid-19 Pandemic" - Anonymous (Entangled Religions - Interdisciplinary Journal for the Study of Religious Contact and Transfer, 2022)
This is the second review of the preprinted article "Jain Life Reimagined: An Examination of Jain Practice and Discourse during the Covid-19 Pandemic." The review will be taken offline once the final article has appeared. The reviewed article can be found under the following link: (PREPRINT) Jain Life Reimagined: An Examination of Jain Practice and Discourse during the Covid-19 Pandemic | Entangled Religions (rub.de)